PENGARUH KOMUNIKASI HORIZONTAL DAN KECERDASAN EMOSIONAL (EQ) TERHADAP KEPUASAN KERJA GURU DI SMP NEGERI 1 PAJO NTB - Nurrahmaniah Nurrahmaniah; Nurjaya Nurjaya (Jurnal Manajemen Pendidikan, 2025)
Job satisfaction is an individual's emotional attitude in the form of feelings of pleasure, satisfaction with a job related to the work situation. Job satisfaction is shown in carrying out tasks that are not in accordance with the responsibilities based on job satisfaction standards in communicating between teachers and teachers, being indifferent to each other, and there are teachers who do not understand each other and only care about themselves without seeing the activities carried out by other teachers and so on in terms of completing tasks done alone without considering assistance from other teachers in the work environment and the lack of emotional intelligence of teachers in terms of self-control when given new tasks and enthusiasm in carrying out their duties so that job satisfaction is not optimal in working. The research method used is a quantitative approach. Sampling was carried out using the population of educators (teachers) of SMP Negeri 1 Pajo NTB. as many as 27 educators (teachers), the data collection technique is using a questionnaire. The data analysis technique used is the multiple linear regression coefficient.